PREVALENCE OF DIABETES IN COMPLETELY EDENTULOUS PATIENTS - A RETROSPECTIVE CROSSSECTIONAL TEACHING HOSPITAL BASED STUDY - Kumar Iyer, Prabhav; Anand Bennis, Marian; Dinesh S.P, Sarvana (International Journal of Psychosocial Rehabilitation, 2020)
Diabetes is one of the most common systemic conditions seen in middle-aged and elderly people in India. It has severe health and lifestyle complications that have a negative impact on the health of the individual, one of them being poor oral health. Numerous studies have shown the correlation between diabetes and periodontal diseases. However, very few studies show a relation between diabetes and edentulism [partial and complete]. The aim of this study was to find a correlation between diabetes and complete edentulism in a hospital-based study. A retrospective descriptive study was conducted using the patient records from June 2019-March 2020, and patients who were diabetic and completely edentulous at the time of the visit at a university dental hospital in Chennai were analyzed. Out of the 62 patients, the age group most commonly associated with complete edentulism was 51-70 years [69.35%], followed by 71+ age groups [17.17%]. The population showed an equal ratio of male to female patients. The most common period of edentulism in the 51-70 age group was 36 months. The same in the 30-50 age group was 3 months, and in the 71+ age group, it was 12 months. Only 4.8% of the patients were smokers. The most common group with complete edentulism was found to be males between the ages of 50 and 70 who had no other systemic conditions except for diabetes and had their period of edentulism to be 36 months, with a prevalence of 11.2%. The study found a significant association between diabetes and duration of edentulism (p = 0.012). The limitations of the study are that other factors that might influence edentulism, such as stress and the socioeconomic status of the patient, were not considered. The results might vary if a larger population with greater geographic diversity is studied. This study showed an association between diabetes and complete edema.